Social identity dimensions as drivers of consumer engagement in social media sports club - Željka Marčinko Trkulja; Jasmina Dlačić; Dinko Primorac (Journal of Risk and Financial Management, 2022)
Consumer engagement is defined as a multidimensional concept in this study via the identification of members of a sports club social network and consumer identification with a sports club brand on social networks. Hence, the study focuses on sports clubs that engage with their customers through social media. The purpose of this paper is to provide a conceptual and theoretical understanding of consumer engagement, particularly among sports teams that employ interactive platforms to establish relationships with customers. Furthermore, in order to better comprehend the interaction between consumer and brand, this research approaches customer identification as consisted of two distinct constructs. Consumer identification with members of a sports club social network is separated from customer identification with a sports club brand. Research results point out that the consumer identification with members of the sports club's social network and consumer identification with the sports club's brand are positively related to consumer engagement. Furthermore, the value creation process is enhanced if the sport club approaches separately different dimensions of customer engagement in the social networks of the sports club.
Keywords: 650; consumer identification; consumer engagement; social networks; sport clubs